Question of protection of water animals in Republic Dagestan - M. B. Bajranbekov; A. A. Abdulmedzhidov (Юг России: экология, развитие, 2015)
The catalodues of protested water non-vetibrates and teir communities havenit been made up till now, eben for tne reserves, national pavts and other catadories of especially protested territories of Dagestan. On the territory of Dagestan there are some faunistic sites, in particular water reservoirs of tne cascade of tne Sulak hydroelectris pover station, upper and mouth parts ancient fresh-water non-vertibrates live, and they shoulg be protested.